PENGARUH TES PENGETAHUAN AWAL TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN DAN STRUKTUR KALIMAT SISWA KELAS VIII MTsN2 DELI SERDANG - Lubis, Raudahtul Sarifah; Hasibuan, Ahmad Laut (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2024)
This research raises the issue of whether there is an influence of the initial knowledge test on the reading comprehension and sentence structure skills of class VIII students at MTs Negeri 2 Deli Serdang in the 2023/2024 academic year? The aim of this research is to determine the effect of the initial knowledge test on the reading comprehension and sentence structure skills of class VIII students at MTs Negeri 2 Deli Serdang. The method used in this research is an experimental method with a simple 2 x 2 factorial design. The population in this research is the entire class VIII of MTs Negeri 2 Deli Serdang, totaling 352 people spread across 11 classes with a research sample of 80 students taken at random. The instrument used is an objective test consisting of 20 multiple choice questions, with a scoring technique that if 1 is correct, a score of 5 is given. So the highest score is 100 and the lowest is 5. The results of the research show that there is an influence of the initial knowledge test on reading comprehension skills and making sentence structures. Class VIII students at MTs Negeri 2 Deli Serdang, with the results of ANOVA calculations obtained Fcount = 6.32 and Ftable = 4.00 at a significance level of 0.05. This shows that Fcount > Ftable. Thus, the hypothesis is accepted. In this way, there is an influence of the initial knowledge test on the reading comprehension and sentence structure skills of class VIII students at MTs Negeri 2 Deli Serdang.